MOLECULAR DOCKING STUDY BETWEEN 3 THAI MEDICINAL PLANTS COMPOUNDS AND COVID-19 THERAPEUTIC PROTEIN TARGETS: SARS-COV-2 MAIN PROTEASE, ACE-2, AND PAK-1 - ASIH, SAFIRA CANDRA; IRDIANI, RAFIDHA; SAHLAN, MUHAMAD; NASIKIN, MOHAMMAD (International Journal of Applied Pharmaceutics, 2021)
Objective: The present study aimed to evaluate those 3 compounds among 122 Thai natural products by using a molecular docking approach to inhibit Main Protease (Mpro) of SARS-CoV-2 (PDB code: 6Y2F), Angiotensin Converting Enzyme (ACE)-2 (PDB code: 1R4L), and PAK-1 kinase (PDB code: 5DEW). Methods: The evaluation was performed on the docking scores calculated using AutoDock Vina as a docking engine and interaction profile analysis through 2-dimensional visualization using LigPlot+. The determination of the docking score was done by selecting the conformation of the ligand that has the lowest binding free energy (best pose). Result: The results of this study indicate that overall, Panduratin A has the best affinity in inhibiting the main protease of SARS-CoV-2, ACE-2, and PAK-1 compared to other compounds. Conclusion: The three thai medicinal plants compound has the potential to be developed as specific therapeutic agents against COVID-19.